Comparisons of heart rate variability responses to head-up tilt with and without abdominal and lower-extremity compression in healthy young individuals: a randomized crossover study - Oyake, Kazuaki; Katai, Miyuki; Yoneyama, Anzu; Ikegawa, Hazuki; Kani, Shigeru; Momose, Kimito (Frontiers in Physiology, 2024)
Introduction: Abdominal and lower-extremity compression techniques can help reduce orthostatic heart rate increases. However, the effects of body compression on the cardiac autonomic systems, which control heart rate, remain unclear. The primary objective of this study was to compare heart rate variability, a reflection of cardiac autonomic regulation, during a head-up tilt test with and without abdominal and lower-extremity compression in healthy young individuals. The secondary objective was to conduct a subgroup analysis, considering participant sex, and compare heart rate and heart rate variability responses to head-up tilt with and without compression therapy. Methods: In a randomized crossover design, 39 healthy volunteers (20 females, aged 20.9 ± 1.2 years) underwent two head-up tilt tests with and without abdominal and lower-extremity compression. Heart rate and heart rate variability parameters were measured during the head-up tilt tests, including the Stress Index, root mean square of successive differences between adjacent R-R intervals, low- and high-frequency components, and low-to-high frequency ratio. Results: Abdominal and lower-extremity compression reduced the orthostatic increase in heart rate (p < 0.001). The tilt-induced changes in heart rate variability parameters, except for the low-frequency component, were smaller in the compression condition than in the no-compression condition (p < 0.001). These results were consistent regardless of sex. Additionally, multiple regression analysis with potentially confounding variables revealed that the compression-induced reduction in Stress Index during the head-up tilt position was a significant independent variable for the compression-induced reduction in heart rate in the head-up tilt position (coefficient = 0.411, p = 0.025). Conclusion: Comparative analyses revealed that abdominal and lower-extremity compression has a notable impact on the compensatory sympathetic activation and vagal withdrawal typically observed during orthostasis, resulting in a reduction of the increase in heart rate. Furthermore, this decrease in heart rate was primarily attributed to the attenuation of cardiac sympathetic activity associated with compression. Our findings could contribute to the appropriate application of compression therapy for preventing orthostatic tachycardia. This study is registered with UMIN000045179.